AB0136 Microparticles from sle patients are a source of interferon-alpha. (15th June 2017) - Miranda, F; Barbati, C; Spinelli, FR; Ceccarelli, F; Truglia, S; Alessandri, C; Valesini, G; Conti, F
Abstract : Background: Systemic lupus erythematosus (SLE) is the prototype of systemic autoimmune disorders. In the late 1970s, increased serum levels of interferon (IFN) were shown for the first time to be significantly associated with SLE and to correlate with disease activity. IFNα is a pleiotropic cytokine that can affect multiple cell types involved in lupus.Plasmacytoid dendritic cells have a special role in the production of IFN and are the main sources of serum interferon. IFN has the potential to dramatically influence the development, progression, and pathogenesis of SLE as it can influence the function and activation state of most major immune cell subsets and function as a bridge between innate and adaptive immunity.Lupus-prone mouse models, indicates that the type I interferon system may play a pivotal role in the pathogenesis of several lupus and associated clinical features, such as nephritis, neuropsychiatric and cutaneous lupus.Circulating microparticles (MPs) are ubiquitous in the blood of healthy individuals, These MPs play an active role in coagulation and intercellular communication and assist in activation or suppression of the immune system, depending on their parental cell origin. Changes in the concentration and/or composition of circulating microparticles have been described in various autoimmune diseases, including rheumatoid arthritis (RA) systemic sclerosis (SSc) and systemic lupus erythematosus (SLE). For SLE, the reported microparticle-related changes remain somewhat inconclusive. Objectives: To better understand the role of MPs in SLE patients, we analyzed the presence of interferon alpha on MPs surface. Methods: MPs were isolated from citrate-treated plasma; blood cells were removed by two steps of centrifugation process (2500g for 15min at 20 C two time). The resulting platelet-poor-plasma (PPP), was analyzed by flow cytometry with specific antibody against IFN alpha Results: 20 consecutive SLE patients (10 with active lupus nephritis) and 10 sex- and age-matched healthy control subjects were included in the study. We found that MPs from SLE patients carry on their surface IFN alpha.Moreover, the percentage IFNalpha + MPs was higher in SLE patients and in lupus nephritis patients than in HC, but there was not significant difference between patients with and without renal involvement. Conclusions: The results of the present study show for the first time the presence of IFN alpha on MPs surface.We may assume that INF+ MPs derive from dendritic cells. In lupus nephritis patients the increased recruitment of dendritic cells was at tubular interstitial level, with subsequent IFN alpha production. Interestingly, MPs (containing RNA and DNA) could stimulate type I IFN production in plasmacytoid dendritic cells and MPs releasing. Disclosure of Interest: None declared